Lethal Bronzing Disease (LBD) - Brian W. Bahder; Ericka E. Helmick; Nigel A. Harrison; Monica L. Elliott (EDIS)
Lethal bronzing disease (LBD), formerly Texas Phoenix Palm Decline (TPPD), is a lethal phytoplasma infection of various palm species in the state of Florida. It was first detected in Florida in 2006 and has since spread to 31 different counties and been isolated from 16 different species of palm. This three-page fact sheet describes the pathogen and hosts of LBD, its symptoms, how to diagnose it, and disease management practices. Written by Brian W. Bahder and Ericka Helmick, and published by the UF/IFAS Plant Pathology Department, May 2019. This article is a minor revision of an earlier fact sheet by Nigel A. Harrison and Monica L. Elliott.